The evolution of He nanobubbles in tungsten under fusion-relevant He ion irradiation conditions. (27th June 2019) - Bi, Zhenhua; Liu, Dongping; Zhang, Yang; Liu, Lu; Xia, Yang; Hong, Yi; Fan, Hongyu; Benstetter, Günther; Lei, Guangjiu; Yan, Longwen
Abstract: He-induced W nanofuzz growth over the W divertor target is one of the main limiting factors affecting the current design and development of fusion reactors. In this paper, based on He reaction rate model in W, we simulate the growth and evolution of He nanobubbles during W nanofuzz formation under fusion-relevant He + irradiation conditions. Our modeling unveils the existence of He nanobubble-enriched W surface layer (<10 nm), formed due to the He diffusion in W crystal into defect sites. At an elevated temperature, the growth of He bubbles in the W surface layer prevents He atoms diffusing into the deep layer (>10 nm). The formation of W nanofuzz at the surface is attributed to surface bursting of high-density He bubbles with their radius of 4 nm, and an increase in the surface area of irradiated W. Our findings have been well confirmed by the experimental measurements.